2018
DOI: 10.1186/s12887-018-1127-6
|View full text |Cite
|
Sign up to set email alerts
|

Practice and outcomes of neonatal resuscitation for newborns with birth asphyxia at Kakamega County General Hospital, Kenya: a direct observation study

Abstract: BackgroundAbout three – quarters of all neonatal deaths occur during the first week of life, with over half of these occurring within the first 24 h after birth. The first minutes after birth are critical to reducing neonatal mortality. Successful neonatal resuscitation (NR) has the potential to prevent these perinatal mortalities related to birth asphyxia. This study described the practice of NR and outcomes of newborns with birth asphyxia in a busy referral hospital.MethodsDirect observations of 138 NRs by 2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
32
1
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 38 publications
(43 citation statements)
references
References 14 publications
(16 reference statements)
2
32
1
1
Order By: Relevance
“…Besides the above, although secretion obstruct babies airway and worsening asphyxia, our findings showed that newborns born with meconium (stained amniotic fluid in the airway who did not start breathing on their own) had no effect on chances of survival after neonatal resuscitation. However, this contradicts with other study done in Kenya [27,28] which demonstrated that meconium presence was a predictor of survival of neonates after neonatal resuscitation. The possible justification could be, competency of health workers were good in airway clearance in presence of meconium in babies who did not start breathing on their own.…”
Section: Discussioncontrasting
confidence: 83%
“…Besides the above, although secretion obstruct babies airway and worsening asphyxia, our findings showed that newborns born with meconium (stained amniotic fluid in the airway who did not start breathing on their own) had no effect on chances of survival after neonatal resuscitation. However, this contradicts with other study done in Kenya [27,28] which demonstrated that meconium presence was a predictor of survival of neonates after neonatal resuscitation. The possible justification could be, competency of health workers were good in airway clearance in presence of meconium in babies who did not start breathing on their own.…”
Section: Discussioncontrasting
confidence: 83%
“…With all the challenges mentioned above, simple investments of procuring and distributing neonatal resuscitation equipment (neonatal size self-inflating bag and mask and suction aspirators) to mid-level health facilities like health centers and clinics can avert many infant deaths due to breathing difficulties at birth. In addition, the availability of health workers who attend delivery and trained in Helping Babies Breathe (HBB) is a crucial step to improve survival of these babies from breathing difficulties [14, 15].…”
Section: Introductionmentioning
confidence: 99%
“…Por otro lado, al evaluar el cuidado del cordón umbilical, después de la intervención hallaron un cumplimiento del 85 %, similar al reportado en el presente estudio. El hallazgo anterior se suma al reportado por Shikuku et al (25) los cuales, en un total de 138 reanimaciones neonatales realizadas en las salas de parto del Hospital General Regional del condado de Kakamega, en Kenia, evidenciaron que en el 100 % de los casos en los que el recién nacido no respondió a la estimulación inicial y el mantenimiento de la vía respiratoria se procedió de forma acertada a suministrar ventilación con bolsa y máscara. En el 71 % de las reanimaciones se mantuvo un ambiente cálido.…”
Section: Discussionunclassified